NUMERICAL AND EXPERIMENTAL STUDY OF A FREE INCOMPRESSIBLE ISOTHERMAL TURBULENT COAXIAL JET - Ströher, G. R.; Martins, C. A.; de Andrade, C. R. (Revista de Engenharia Térmica, 2010)
In the present study the free incompressible isothermal turbulent coaxial jet problem is numerically solved, and compared with experimental measurements for different velocity ratio between the inner and the outer streams of the jet. The radial profile of the axial mean velocity was obtained with hot anemometry at different axial positions. Governing equations (mass conservation, momentum, turbulence model) were discretized employing the finite volume method with a segregated solver. The analysis of the experimental results showed that coaxial jet flow fields did not present self-similarity up to z/D=25, and the numerical solution using the Shih’s k ε turbulence model did not match reasonably with the experimental data, with a difference of about ± 10%.